Phytochemicals and antimicrobial properties of traditional medicinal plants in Bosnia and Herzegovina - Ibragić, Saida; Dahija, Sabina; Bešta-gajević, Renata; Durak, Selma; Garbo, Hava; Karalija, Erna (Journal of Research in Pharmacy, 2025)
In traditional medicine, plants are widely utilized as sources of bioactive compounds for treating various diseases. This study aimed to evaluate the secondary metabolite composition, antioxidant properties, and antimicrobial effects of 38 medicinal plants commonly used in Bosnia and Herzegovina. Plants were collected from natural habitats, and dried plant material from different organs, selected based on their traditional medicinal use, was used for the extraction of bioactive compounds with 80% ethanol. The extracts were analysed for phenolic, flavonoid, and tannin content, as well as antioxidant capacity (using DPPH and FRAP assays) and antimicrobial activity. The antimicrobial activity of all 38 plants was initially screened using the disc diffusion method. For plants showing significant antimicrobial activity (inhibition zones > 20 mm), the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. All analysed plants exhibited high phenolic content, with Melissa officinalis leaf extract, Filipendula vulgaris flower extract, and Rubus plicatus leaf extract containing over 300 mg GAE/g DW. According to the DPPH assay, high antioxidant capacity was observed in extracts from the leaves of Fragaria vesca, Prunus armeniaca, Rubus plicatus, and R. ideus, as well as in Rosa canina fruit and Filipendula vulgaris flower extracts, with values reaching 702.39 mg TE/g DW. Among the 38 tested plants, 16 exhibited high antimicrobial activity with inhibition zones greater than 20 mm. To ensure both the efficacy and safety of these plants, further studies on their toxicity, particularly dose-dependent toxicity, are necessary.